2014
DOI: 10.1371/journal.pone.0105829
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Property of Symplocos cochinchinensis Is Mediated by Inhibition of Alpha Glucosidase and Enhanced Insulin Sensitivity

Abstract: The study is designed to find out the biochemical basis of antidiabetic property of Symplocos cochinchinensis (SC), the main ingredient of ‘Nisakathakadi’ an Ayurvedic decoction for diabetes. Since diabetes is a multifactorial disease, ethanolic extract of the bark (SCE) and its fractions (hexane, dichloromethane, ethyl acetate and 90% ethanol) were evaluated by in vitro methods against multiple targets relevant to diabetes such as the alpha glucosidase inhibition, glucose uptake, adipogenic potential, oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Depletion of antioxidant level has been demonstrated in DM and administration of antioxidants to compensate the depletion has been shown to improve diabetes and prevent its complications [76]. It is hypothesized that under severe oxidative stress (such as in DM), there is heavy production of reactive species which may result in the depletion of protective physiological moieties [68].…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of antioxidant level has been demonstrated in DM and administration of antioxidants to compensate the depletion has been shown to improve diabetes and prevent its complications [76]. It is hypothesized that under severe oxidative stress (such as in DM), there is heavy production of reactive species which may result in the depletion of protective physiological moieties [68].…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemicals such as flavonoids in aqueous preparation of plants have shown to possess antidiabetic and antioxidant activities (Sharma et al 2009;Jaiswal et al 2013). The present study suggested that the aqueous fraction of P. fulgens roots might exhibit antidiabetic properties by slowing down the assimilation of carbohydrate, ameliorating postprandial hyperglycemia and increased the insulin sensitivity, mainly due to its ability to inhibit the intestinal α-glucosidase activity (Antu et al 2014). Thus, active compounds could be isolated from an aqueous fraction of P. fulgens roots, which might be used as a lead compound for the development of antidiabetic therapeutics.…”
Section: Discussionmentioning
confidence: 78%
“…Decrease in blood glucose and increase in plasma insulin and liver glycogen, decrease in serum TC, TG, LDL-C levels and increase in HDL-C, restored the altered plasma enzymes (SGOT, SGPT and ALP), total protein, urea and creatinine levels [340] Bark extract α-glucosidase inhibition, insulin dependent glucose uptake in L6 myotubes, pancreatic beta cell regeneration in RIN-m5F and reduced triglyceride accumulation in 3T3L1 cells, protection from hyperglycemia induced the generation of reactive oxygen species in HepG2 cells with moderate antiglycation and PTP-1B inhibition [341] Portulacaceae Talinum portulacifolium Forssk.…”
Section: Bark Extractmentioning
confidence: 98%